The functional role of prostaglandin E2 in cigarette smoke-induced inflammation and exacerbated responses to bacterial challenge - Beaulieu, Ashley (My University, 2016)
Cigarette smoking is the main etiological factor for the development of COPD, an inflammatory disease characterized by progressive and irreversible airflow limitation. Bacterial infections trigger disease exacerbation and accelerate the decline in lung function seen in COPD patients. Recent attempts to further the understanding of molecular mechanisms underlying the pathogenesis of COPD have outlined a skewed release of lipid mediators of inflammation from the COPD-afflicted lung. Among these lipid mediators, pulmonary levels of PGE2 are increased in COPD patients, and even more pronounced increases in PGE2 are observed during disease exacerbation. Although PGE2 is capable of exerting both pro- and anti-inflammatory effects depending on the context of inflammation, its role in the chronic inflammatory processes observed in COPD has yet to be elucidated. Therefore, we aimed to investigate the functional relevance of PGE2 in cigarette smoke-induced inflammation and bacterial exacerbations of these inflammatory responses. Using a well-characterized murine model of cigarette smoke-induced inflammation and bacterial infection, we found that cigarette smoke exposure and NTHi infection elevate levels of PGE2 in the lungs of mice, through upregulation of mPGES-1. Moreover, utilizing mPGES-1-deficient mice, we showed that PGE2 attenuated pulmonary cellular inflammation in response to cigarette smoke exposure and NTHi infection. We found that this attenuated inflammation was not due to the actions of SOCS3, as expression of SOCS3 was redundant of PGE2. Finally, while we discovered that PGE2 enhanced the phagocytic abilities of cigarette smoke-exposed alveolar macrophages, it did not affect the dynamics of pulmonary NTHi clearance from smoke-exposed mice. Overall, the data presented here indicate that PGE2 likely plays an anti-inflammatory role in response to cigarette smoke exposure and bacterial infection, and direct the focus of future investigations with regards to the use of PGE2 as a potential therapeutic target for the treatment of COPD.